UnPAKing RUNX3 functions–Both sides of the coin. (4th July 2019) - Kumar, Arun; Sundaram, Sandhya; Rayala, Suresh K.; Venkatraman, Ganesh
ABSTRACT: Post translational modifications of RUNX3 have been shown to play an important role in directing RUNX3 functions. In this review we highlight the phosphorylation dependent functions of RUNX3 as regulated by PAK1 and its implications on tumorigenesis.